COHERENCE ANALYSIS OF THE STUDENTS' WRITINGS: A CASE STUDY OF THE 4TH SEMESTER STUDENTS OF ENGLISH DEPARTMENT, FACULTY OF LANGUAGES AND LETTERS DIAN NUSWANTORO UNIVERSITY - Setyo Prasiyanto Cahyono (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2011)
The title of this research is coherence analysis of the students writing: a case study of the fourth semester students of English Department, Faculty of Language and Letter Dian Nuswantoro University. This analysis is conducted to know the coherence of students' writings that are made by the fourth semester students in writings class. The study of this research is descriptive qualitative, which includes a simple quantitative study. The subject of this research is the students' writings by twenty students in Faculty of Language and letters Dian Nuswantoro University, in Academic years 2003/2004.The result of the data reveals that all the texts which have been analyzed are coherent and the content was relevant to the topic “unforgettable experience. There were only four texts showing that the content was not relevant to the topic sentence. Most of the students employed the thematic progression of theme reiteration or constant theme pattern in their writing. Keywords: coherence, students' writings, thematic progression